Identifying tumour associated macrophages and microglia in an experimental glioblastoma model. (31st January 2018) - Youshani, Amir Saam; Yu, Kenny; Wilkinson, Fiona; O'leary, Claire; Cook, Peter; Liao, Aiyin; Pathmanaban, Omar; Waugh, Chris; Shorrock, Hannah; Macdonald, Andrew; Roncaroli, Federico; Kamaly-asl, Ian; et al.
Abstract: Glioblastoma is the most aggressive primary brain cancer, with 14.6 months median survival. Tumour associated macrophages and microglia (TAMM) populate upto 40% of the tumour bulk and represent potential immunotherapy targets. Characterising functional roles of TAMM subpopulations remains elusive due to limitations of existing mouse models and cross-reactive cell-surface markers. We identify a new marker-set using flow cytometry that distinguishes between peripheral macrophages and brain microglia in glioblastoma. Using non-myeloablative busulfan conditioning, we transplant mice expressing the pan leukocyte epitope CD45.1 with haematopoietic donor cells expressing congenic CD45.2, without damaging the recipient blood-brain barrier. Once 90% bone marrow chimerism is achieved at 12 weeks with no brain macrophage repopulation, we stereotactically implant GL261 murine glioblastoma cells into brain of chimeric mice, recapitulating normal tumour development. Brain flow cytometry using a 15-marker panel was then used to identify different immune cell populations and characterise TAMM subpopulations. We identify multiple immune populations migrating to tumours, and demonstrate that marker sets such as CD11b/CD45 and Siglec-H/CX3CR1, used to distinguish between microglia and macrophages, have significant co-staining from other leukocyte populations (both donor and recipient). Importantly we identify a novel 4-marker set that separates TAMM into four subpopulations with ≥ 90% donor/recipient purity, including monocytes, undifferentiated and differentiated macrophages, and microglia. In conclusion, we have developed a novel chimeric mouse model that achieves superior levels of peripheral chimeras, yet retains a homeostatic brain. Our results also highlighted a new 4-marker approach to subcategorising TAMM. RNA sequencing of TAMM subpopulations and downstream transcriptional analysis will provide the first insight into the functional role of TAMM. Further work will necessitate applying this marker set to human glioblastoma specimens, and validate our findings from an experimental glioblastoma model.